Studying the influence of design and operation mode parameters on efficiency of the systems of biochemical purification of emissions - Bakharevа Anna; Shestopalov, Oleksii; Filenko, Olesya; Tykhomyrova, Tetyana; Rybalova, Olga; Artemiev, Sergey; Bryhada, Olena (Eastern-European Journal of Enterprise Technologies, 2018)
A procedure for evaluating efficiency of the systems of biological elimination of soluble and insoluble in water harmful gaseous substances as well as dissolved in water contaminants has been devised. The procedure is based on previously developed mathematical models of the corresponding non-stationary bio oxidation processes. Based on the analysis of 27 design versions, real capabilities of biological purification facilities were shown, the effect of design and operation mode parameters on efficiency of the systems of biological destruction of methane, hydrogen sulfide and formaldehyde were assessed. In quantitative terms, the results obtained in numerical experiments indicate the necessity of taking into account variation of the rate of pollutant inflow in the process of vessel filling. It was established that an increase in the facility efficiency in terms of the volume of the gas-air mixture, N, causes a decrease in methane concentration at the bioreactor entry and a reduction of the purification degree to 62 %. An increase in the rate of hydrogen sulfide inflow to the reactor leads to a reduction of the purification degree from 98 to 95 %. An increase in the initial concentration of biomass by a factor of 1.7 causes a decrease in concentration of hydrogen sulfide in water from 2.5 to 1.1 g/m3. A significant decrease in the average specific bio oxidative power with an increase in the working space in which the final stage of emission purification from formaldehyde takes place was also observed. The revealed regularities represent a tool for improving quality of design solutions and increasing effectiveness of bio oxidation modes in operation of the systems of biological gas purification.